Building institutional capacities for students as partners in the design of COVID classrooms - Riddell, Jessica; Gadoury-Sansfaçon, Georges-Philippe; Stoddard, Scott (International Journal for Students as Partners, 2021)
The COVID-19 pandemic in 2020 posed several challenges to post-secondary institutions, including the move to online learning in a short amount of time. In June 2020, Bishop’s University hired 23 students as online learning and technology consultants (OLTCs) to help faculty prepare for Fall 2020. They underwent training about Students-as-Partners literature, empathetic design, pandemic pedagogy, high-impact practices, and authentic learning design. After their training—which included online modules, simulations, faculty mentorship, and technology training—the program launched in July 2020. In this case study, we deploy SaP literature to solve pedagogical challenges posed by the pandemic, analyze the data collected in the program’s developmental assessment, and share the program’s impact on students, faculty, and the institution more broadly. This program is a key intervention in building institutional capacities for SaP work in a post-COVID higher education context. The outcomes of this case study demonstrate that working with students as partners in the design of COVID classrooms increases students’ social and emotional intelligence, technical and digital literacy skills, critical thinking, project management skills, and other significant learning gains.